Implications of Local Regulations on Street Vendors for Corporate Partners of Micro and Small Business in Depok City - Syahuri, Taufiqurrohman; Surahmad; Thohari, Ahmad Ahsin; Fauzan, Muhammad; Maula, Putri Ni'matul; Tobing, Vania Athalia Lumban (Al-Risalah, 2026)
This study focuses on the impact of local regulations governing street vendors on corporate partners and micro, small, and medium enterprises (MSMEs) in Depok City. In this context, street vendors play an important role in the local economy and require regulation to ensure sustainability and proper management of public spaces. This study aims to analyze how the implementation of the Perda affects corporate cart partners and MSMEs, with the goal of identifying the challenges and opportunities faced by these businesses. The research method used is a normative legal approach supplemented by in-depth interviews to obtain rich and detailed data from MSMEs, PKL, corporate partners, and relevant stakeholders. This study also employs policy analysis using a legal and conceptual approach to evaluate the effectiveness of existing regulations. The results and discussion reveal that SME partners strongly agree with the on-the-ground conditions in Depok City, where frequent raids on SMEs significantly hinder their economic activities. However, on the other hand, based on interviews with the team from the Depok City Cooperative and SME Department, it was explained that SMEs that are raided need to be mentored to gain knowledge and understanding regarding Depok City Regulation No. 3 of 2024 on the Protection, Empowerment, Development of Micro Businesses, as well as the Regulation and Empowerment of Street Vendors. This will at least provide protection and meet the needs of SMEs in Depok City. Thus, the implications of this regulation have a positive impact on SMEs and street vendors in driving the economy of Depok City.